2018
DOI: 10.15436/2379-1705.18.1685
|View full text |Cite
|
Sign up to set email alerts
|

Implant-Supported Screw-Retained Vs Cemented Single Crown Fabricated By CAD / CAM Technology: A Clinical Case Report

Abstract: CAD/CAM technologies in Dental Implantology present opportunities for preliminary implant planning, surgical template design, guided surgery and fabrication of immediate and permanent implant-supported restorations. The aim of this publication is to compare two types of implant-supported single crowns-screw-retained and cemented, illustrated with a clinical case. Advantages and disadvantages of the both types of restorations are described. The choice between screw-retained and cemented implant-supported restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…8). The preliminary results reported in this article support the findings of studies published by Lanis et al (2015), Pozzi et al (2016), and Vlahova et al (2017and 2018 in that, a combination of digital surface scanners and CT's facilitates the predictability of the results in guided implant surgery.…”
Section: Resultssupporting
confidence: 87%
“…8). The preliminary results reported in this article support the findings of studies published by Lanis et al (2015), Pozzi et al (2016), and Vlahova et al (2017and 2018 in that, a combination of digital surface scanners and CT's facilitates the predictability of the results in guided implant surgery.…”
Section: Resultssupporting
confidence: 87%
“…In a systematic review and meta-analysis of comparative studies between subtractive CAD/CAM materials for provisional non-permanent prosthodontics (PNPCs) and conventional materials, Jain et al concluded that 3D-printed provisional crowns and materials for removable prosthetics could be used as an alternative to long-term conventional and CAD/CAM subtractive materials [40,41].…”
Section: Summary Of the Main Trendsmentioning
confidence: 99%